2012
DOI: 10.5007/2175-7925.2012v25n4p49
|View full text |Cite
|
Sign up to set email alerts
|

Vigor e viabilidade de sementes de trigo tratadas com zinco

Abstract: ResumoO zinco tem sido utilizado na formulação de produtos denominados fitoestimulantes, atuando no alongamento celular e formação de raízes laterais. Dessa forma, este trabalho teve como objetivo avaliar o efeito de doses de zinco aplicadas em tratamento de sementes sobre a germinação e o vigor de cultivares de trigo. O experimento constou de duas cultivares de trigo (Quartzo e Supera) e sete doses de zinco aplicadas em tratamento de sementes na forma ZnSO 4 .7H 2 O (0; 0,19; 0,38; 0,76; 0,95; 1,14; e 1,52g d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
3
0
2
Order By: Relevance
“…There was no significant difference regarding the increase in doses used for germination variable (Table 2). These results are in agreement with those found by Ohse et al (2012), by concluding that the zinc doses applied via seed treatment did not affect the germination of seeds of wheat cultivars. Also Funguetto et al (2010), working with rice seeds coated with zinc sulfate, found no differences in germination.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There was no significant difference regarding the increase in doses used for germination variable (Table 2). These results are in agreement with those found by Ohse et al (2012), by concluding that the zinc doses applied via seed treatment did not affect the germination of seeds of wheat cultivars. Also Funguetto et al (2010), working with rice seeds coated with zinc sulfate, found no differences in germination.…”
Section: Resultssupporting
confidence: 93%
“…Some studies have already demonstrated the influence of Zn application on physiological performance of seeds such as rice (Funguetto et al, 2010), sorghum (Yagi et al, 2006Santos et al, 2008), wheat (Ohse et al, 2012), among others.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the comparison between two cultivars, it is a common approach in experiments that evaluate the performance of seeds subjected to a treatment with nutrients. Several surveys have been conducted in this way, assessing several varieties and their responses to the application of nutrients -such as the works by Tavares et al with barley seeds 43 and rice 44 , the one by Ohse, Cubis 45 with wheat seeds or that by Queiroga, de Queiroz Castro 46 with cotton seeds, to name a fewand significant differences between cultivars were also found, as in the study reported herein.…”
Section: Discussionmentioning
confidence: 69%
“…The higher percentage of zinc present in micronutrient 1 may have contributed to these results. Ohse et al (2012) observed a 31.63% increase in shoot fresh mass of corn plants submitted to seeds treatment with 0.86 g.kg -1 of Zn. These same authors observed a decreasing in root fresh phytomass with the increase in zinc doses, suggesting a probable toxicity due to the excess of the micronutrient.…”
Section: Resultsmentioning
confidence: 88%